# Bosnian

Newest questions and responses by Bosnian-
## Calculus

[ 1 / ( x + h + 1 ) - 1 / ( x + 1 ) ] / h = [ x + 1 - ( x + h + 1 ) ) / ( ( x + h + 1 ) ∙ ( x + 1 ) ] / h = [ x + 1 - x - h - 1 ) / ( ( x + h + 1 ) ∙ ( x + 1 ) ] / h = - h / [ ( x + h + 1 ) ∙ ( x + 1 ) ] / h = - h / [ h ∙ ( x + h + 1 ) ∙ ( x + 1

*posted on January 17, 2019* -
## Math

I guess the question is about cross multiply. 9 ∙ 6 / 18 ∙ 3 = 54 / 54 = 1

*posted on January 15, 2019* -
## math

In Cartesian coordinate system horizontal coordinate is called abscissa. Vertical coordinate is called ordinate. The coordinates do not necessarily have to be x and y. In this case abscissa is x , ordinate is c.

*posted on January 14, 2019* -
## math

x = 0 c = 20 • 0 +150 = 0 + 150 = 150 x = 50 c = 20 • 50 +150 = 1000 + 150 = 1150 Draw Cartesian coordinate system x , c(x) Mark points x = 0 , c = 150 and x = 50 , c = 1150 and draw straigth line between the points.

*posted on January 14, 2019* -
## Math

x = average A = Amy's points = x - 3 B = Brad's points = x - 6 C = Cara's points = x + 5 D = Don 's points = 28 Average: x = ( A + B + C + D ) / 4 Put members of a team points in this equation. x = ( x - 3 + x - 6 + x + 5 + 28 ) / 4 x = ( 3 x + 24 ) / 4

*posted on January 11, 2019* -
## Math

In google paste: A factory can produce two products, x and y, with a profit approximated by P = 14x + 22y – 900. The production of y must exceed the production of x by at least 100 units. Moreover, production levels are limited by the formula x + 2y ≤

*posted on January 10, 2019* -
## math

Slope intercept form equation of straight line: y = m x + b where: m is the slope b is the y-intercept In tis case: 1. ( 8 , 3 ) mean x = 8 , y = 3 m = 5 y = 5 x + b You know coordinates of one point ( 8 , 3 ) Replace x = 8 , y = 3 in equation: y = 5 x + b

*posted on January 10, 2019* -
## math

4 x - 7 y = 3 - x - 7 y = 15 ___________ 4 x - x - 7 y - ( - 7 y ) = 3 - 15 3 x = - 12 Divide both sides by 3 x = - 12 / 3 x = - 4 Replace x = - 4 in equation x-7y=15 - 4 - 7 y = 15 Add 4 to both sides - 4 - 7 y + 4 = 15 + 4 - 7 y = 19 Divide both sides by

*posted on January 7, 2019* -
## algebra

One my typo: not Subtract 20 m to both sides 20 m + 600 - 20 = 23 m - 20 m4 than Subtract 20 m to both sides 20 m + 600 - 20 m = 23 m - 20 m

*posted on January 7, 2019* -
## algebra

m = the amount she had originally She spent: 1 / 8 of her money = m / 8 to buy books 1 / 5 of her money = m / 5 in purchasing clothes and 1 / 10 of her money = m / 10 in purchasing clothes She spent total: m / 8 + m / 5 + m / 10 Rest of money = m - ( m / 8

*posted on January 7, 2019* -
## math

You answer is correct.

*posted on January 5, 2019* -
## Precalculus

First try google then jiskha. Paste your question in google. On c a . y a h o o you will find solution with detail explanation.

*posted on January 5, 2019* -
## math

When you move some variable on other side of equation you must change sign. 24 x + 12 = 7 x² + 7 x is same 24 x + 12 - ( 24 x + 12 ) = 7 x² + 7 x - ( 24 x + 12 ) 0 = 7 x² + 7 x - ( 24 x + 12 ) 0 = 7 x² + 7 x - 24 x - 12 7 x² + 7 x - 24 x - 12 = 0

*posted on January 4, 2019* -
## Math

y – 3 = 4 / 9 ( x – 9 ) add 3 to both sides y – 3 + 3 = 4 / 9 ( x – 9 ) + 3 y = ( 4 / 9 ) ∙ x – ( 4 / 9 ) ∙ 9 + 3 y = ( 4 / 9 ) x – 4 + 3 y = ( 4 / 9 ) x – 1 Answer D is correct.

*posted on January 4, 2019* -
## math

Two consecutive integers are x and x + 1 1 / x + 1 / ( x + 1 ) = 7 / 12 ( x + 1 + x ) / [ x ∙ ( x + 1 ) ] = 7 / 12 ( 2 x + 1 ) / ( x² + x ) = 7 / 12 12 ∙ ( 2 x + 1 ) = 7 ∙ ( x² + x ) 24 x + 12 = 7 x² + 7 x 0 = 7 x² + 7 x - 24 x - 12 0 = 7 x² -

*posted on January 4, 2019* -
## Math

y = m x + b Where: m is the slope b is the y-intercept In tis case: y = ( 4 / 9 ) x + b You know coordinates of one point ( 9 , 3 ) Replace x = 9 , y = 3 in equation: y = ( 4 / 9 ) x + b 3 = ( 4 / 9 ) ∙ 9 + b 3 = 4 + b Subtact 4 to both sides 3 - 4 = 4 +

*posted on January 4, 2019* -
## math

1st / 2nd = 3rd / 4th ( 4 / 5 ) : ( 10 / 13 ) = 4 ∙ 13 : ( 5 ∙ 10 ) = 52 : 50 = 2 ∙ 26 : 2 ∙ 25 = 26 / 25 ( 7 / 8 ) : ( 15 / 18 ) = 7 ∙ 18 : ( 8 ∙ 15 ) = 126 : 120 = 6 ∙ 21 : 6 ∙ 20 = 21 / 20 ( 1 / 2 ) : ( 14 / 28 ) = ( 1 / 2 ) : ( 14 / 14

*posted on January 3, 2019* -
## Math

y = | 5 x | - 2 mean: y = ± 5 x - 2 1. y = 5 x - 2 2. y = - 5 x - 2 These are two straight lines. Find x and y intercepts for both. x- intercept is a point on the graph where y is zero y- intercept is a point on the graph where x is zero 1. y = 5 x - 2 x-

*posted on January 3, 2019* -
## math

If your expression mean: 2 / 3 ∙ 3 / 5 ∙ 5 / 10 ∙ 6 / 8 then: 2 / 3 ∙ 3 / 5 ∙ 5 / 10 ∙ 6 / 8 = 2 ∙ 3 ∙ 5 ∙ 6 / 3 ∙ 5 ∙ 10 ∙ 8 = 180 / 1200 = 60 ∙ 3 / 60 ∙ 20 = 3 / 20

*posted on December 31, 2018* -
## Math

Remark: e ^ ln ( a ) = a So: e^ ln ( 5 x + 7 ) = 5 x + 7 ____________________ ln ( 5 x + 7 ) = 8 Cancel logarithms by taking expof both sides. e^ ln ( 5 x + 7 ) = e ^ 8 5 x + 7 = e ^ 8 Subtract 7 to both sides 5 x + 7 - 7 = e ^ 8 - 7 5 x = e ^ 8 - 7 Divide

*posted on December 31, 2018* -
## Math

You did not write the answer D. But: 0.84 n = n - 0.16 n 0.16 n = 16 % of n The value of his investment decreased by 16% during this time period.

*posted on December 28, 2018* -
## Maths

If your expression mean: ( 3 + i √5 ) ( 3 - i √5 ) / [ ( √3 + √2 i ) - ( √3 - i √2 ) ] then: [ ( 3 + i √5 ) ∙ ( 3 - i √5 ) ] / [ ( √3 + √2 i ) - ( √3 - i √2 ) ] = [ 3 ∙ 3 + 3 ∙ i √5 - i √5 ∙ 3 - i √5 ∙ i √5 ] / [

*posted on December 23, 2018* -
## Math

5 h – 9 = – 16 + 6 h Subtract 5 h to both sides 5 h – 9 - 5 h = – 16 + 6 h - 5 h – 9 = – 16 + h Add 16 to both sides – 9 + 16 = – 16 + h + 16 7 = h h = 7 Answer C.

*posted on December 19, 2018* -
## Math

m – 7 < 6 Add 7 to both sides m – 7 + 7 < 6 + 7 m < 13 Answer C.

*posted on December 19, 2018* -
## Math

C = 5 / 9 ( F - 32 ) Multiply both sides by 9 9 C = 5 ( F - 32 ) Divide both sides by 5 9 / 5 C = F - 32 Add 32 to both sides 9 / 5 C + 32 = F - 32 + 32 9 / 5 C + 32 = F F = 9 / 5 C + 32

*posted on December 17, 2018* -
## Math

F(C) = 9 / 5 C + k − 40º F = 9 / 5 ∙ ( - 40°C ) + k Mathematically: − 40 = 9 / 5 ∙ ( - 40 ) + k − 40 = 9 ∙ ( - 40 ) / 5 + k − 40 = - 360 / 5 + k − 40 = - 72 + k Add 72 to both sides − 40 + 72 = - 72 + k + 72 32 = k k = 32

*posted on December 16, 2018* -
## Math

- 2 ( y - 3 ) = 2 y - 6 - 2 ∙ y - 2 ∙ ( - 3 ) = 2 y - 6 - 2 y + 6 = 2 y - 6 Subtract 2 y to both sides - 2 y + 6 - 2 y = 2 y - 6 - 2 y - 4 y + 6 = - 6 Subtract 6 to both sides - 4 y + 6 - 6 = - 6 - 6 - 4 y = - 12 Divide both sides by - 4 y = - 12 / - 4

*posted on December 16, 2018* -
## Math

2 e³ ∙ 2 e⁵= 2 ∙ 2 ∙ e³⁺⁵ = 4 e⁸

*posted on December 15, 2018* -
## math

yes n = ± 10 1. - n / 10 = 1 - n = 10 ∙ 1 = 10 n = - 10 2. n / 10 = 1 n = 10 ∙ 1 = 10

*posted on December 14, 2018* -
## algebra

2 / 3 - n ∙ 5 / 8 = 7 / 12 2 / 3 - 5 n / 8 = 7 / 12 8 ∙ 2 / 8 ∙ 3 - 3 ∙ 5 n / 3 ∙ 8 = 2 ∙ 7 / 2 ∙ 12 16 / 24 - 15 n / 24 = 14 / 24 Subtract 16 / 24 to both sides 16 / 24 - 15 n / 24 - 16 / 24 = 14 / 24 - 16 / 24 - 15 n / 24 = - 2 / 24

*posted on December 14, 2018* -
## Math

Also you can do this: sin x ∙ tan x = cos x sin x ∙ sin x / cos = cos x sin² x / cos = cos x Multiply both sides by cos x sin² x = cos² x For x = - 2 π sin ( - 2 π ) = 0 , cos ( - 2 π ) = 1 sin² ( - 2 π ) = 0 ≠ cos² ( - 2 π ) 0 ≠ 1² 0

*posted on December 14, 2018* -
## Math

For x = - 2 π sin ( - 2 π ) = 0 , cos ( - 2 π ) = 1 , tan ( - 2 π ) = 0 sin ( - 2 π ) ∙ tan ( - 2 π ) = 0 ∙ 0 = 0 ≠ cos ( - 2 π ) 0 ≠ 1 For x = - 3 π sin ( - 3 π ) = 0 , cos ( - 3 π ) = - 1 , tan ( - 3 π ) = 0 sin ( - 3 π ) ∙ tan ( -

*posted on December 14, 2018* -
## Math

There are just two correct answers. B and E. - 2.5 ( 1 - 2 n ) - 1.5 n = - 2.5 ∙ 1 - 2.5 ∙ ( - 2 n ) - 1.5 n = - 2.5 + 5 ∙ n - 1.5 n = - 2 .5 + 3.5 n = 3.5 n - 2.5 If you analyse all offered answers: A: - 2.5 - 3.5 n = - 3.5 n - 2.5 not equal 3.5 n -

*posted on December 13, 2018* -
## Math

Your answers is correct becouse: - 2.5 ( 1 - 2 n ) - 1.5 n = - 2.5 ∙ 1 - 2.5 ∙ ( - 2 n ) - 1.5 n = - 2.5 + 5 ∙ n - 1.5 n = - 2 .5 + 3.5 n = 3.5 n - 2.5 Answer B: - 2.5 + 3.5 n = 3.5 n - 2.5 Answer E: - 2.5 + n ( 5 - 1.5 ) = - 2.5 + n ∙ 3.5 = - 2.5

*posted on December 13, 2018* -
## Algebra

y = y 1 / 4 x - 4 = - 7 / 4 x + 4 Add 7 / 4 x to both sides 1 / 4 x - 4 + 7 / 4 x = - 7 / 4 x + 4 + 7 / 4 x 8 / 4 x - 4 = 4 2 x - 4 = 4 Add 4 to both sides 2 x - 4 + 4 = 4 + 4 2 x = 8 Divide both sides by 2 x = 8 / 2 x = 4 Replace this value in equation

*posted on December 12, 2018* -
## math

6 % = 6 / 100 $1,800 ∙ 6 % = 1,800 ∙ 6 / 100 = $10800 / 100 = $108 OR 6 % = 6 / 100 = 0.06 $1,800 ∙ 6 % = $1,800 ∙ 0.06 = $108

*posted on December 12, 2018* -
## math

An integer is a whole number, positive or negative. A rational number is a number which can be expressed as a fraction between two whole numbers. Every integer is a rational number, because every integer can be expressed as a fraction between itself and 1,

*posted on December 12, 2018* -
## Math

Correct answer. It's usually written: C = 3.43 G

*posted on December 12, 2018* -
## Science

1 oxide mean monoxide N₂O is dinitrogen monoxide

*posted on December 11, 2018* -
## Science

NH₄NO₃ -> 2H₂O + N₂O

*posted on December 11, 2018* -
## Math

Answers 2 , 3 and 5 are correct. You probably not write question 4 correct because: - 2 ( m - 30 ) = 6 m - 2 ∙ m - 2 ∙ 30 = 6 m - 2 m - 60 = 6m Add 60 to both sides - 2 m - 60 + 60 = 6m + 60 - 2 m = 6 m + 60 Subtract 6 m to both sides - 2 m - 6 m = 6 m

*posted on December 11, 2018* -
## Math

Your answer is correct. - 9 p - 17 = 10 Add 17 to both sides - 9 p - 17 + 17 = 10 + 17 - 9 p = 27 Divide both sides by - 9 p = 27 / - 9 p = - 3

*posted on December 11, 2018* -
## Physics

a = g ( m2 - μk m1 ) / ( m1 + m2 ) = 9.81 ∙ ( 5 - 0.395 ∙ 3 ) / ( 5 + 3 ) = 9.81 ∙ ( 5 - 1.185 ) / 8 = 9.81 ∙ 3.815 / 8 = 37.42515 / 8 = 4.67814375 a = 4.68 m / s² rounded on two decimal pieces

*posted on December 11, 2018* -
## Math

You're right. By the way, the solutions of your your quadratic equations are: x = - 31 / 2 and x = 3 / 2 Length can not be negative so x = 3 / 2 = 1.5 m

*posted on December 11, 2018* -
## math

Both answer are correct.

*posted on December 11, 2018* -
## algebra

33 1/ 3 = 33 * / 3 + 1 / 3 = 99 / 3 + 1 / 3 = 100 / 3 ( 100 / 3 ) / 100 = 100 / 3 * 100 = 100 / 300 = 1 / 3 ( 1 / 3 ) p = 19 Multiply both sides by 3 p = 19 * 3 = 57

*posted on December 10, 2018* -
## pre-algebra

66 2/3 = 66 * 3 / 3 + 2 / 3 = 198 / 3 + 2 / 3 = 200 / 3 66 2/3% = ( 200 / 3 ) / * 100 = 200 / 3 * 100 = 200 / 300 = 2 / 3 87 * 2 / 3 = 174 / 3 = 58

*posted on December 10, 2018* -
## pre-algebra

Correct

*posted on December 10, 2018* -
## math

front wheel's circumference = d π rear wheel's circumference = ( d + 6 ) π ( d + 6 ) π - d π = π ∙ d + π ∙ 6 - d π = d ∙ π + 6 ∙ π - d π = d π - d π + 6 ∙ π = 6 π

*posted on December 5, 2018* -
## math

11.3 x + 7.2 = 86.3 Subtract 7.2 to both sides 11.3 x + 7.2 - 7.2 = 86.3 - 7.2 11.3 x = 79.1 Divide both sides by 11.3 x = 79.1 / 11.3 x = 7

*posted on December 5, 2018* -
## math

Are you kidding? y + 2 y + 3 z = 3 y + 3 z

*posted on December 3, 2018* -
## math

1. Correct 2. y + 2 y + 3 z = ( y + 2 y ) + 3 z = 3 y + 3 z = 3 ( y + z ) 3. Correct 4. Correct 5. Correct

*posted on December 3, 2018* -
## maths

Think of a pie having 50 slices. The first 12 slices are the people taking neither language. The next 25 slices are the people taking Hindi. The next 16 slices are those taking Marathi. ( 12 + 25 + 16 ) slices = 53 slices Three slice too many. Thus the

*posted on November 30, 2018* -
## Math

w = weight of a chicken five times the weight of a chicken = 5 w Your algebraic expression : 8 < 5 w

*posted on November 30, 2018* -
## maths

1 km = 1000 m 1 hm = 100 m 2 km = 2 ∙ 1 000 m = 2 000 m 5 hm = 5 ∙ 100 m = 500 m 2 km 5 hm 8 m = 2 000 m + 500 m + 8 m = 2 508 m 1 254 rotations cover = 2 508 m 1 revolution covers = 2 508 / 1 254 = 2 m Circumference = 2 m

*posted on November 30, 2018* -
## math

13 x - 7 = 136 Add 7 to both sides 13 x - 7 + 7 = 136 + 7 13 x = 143 Divide both sides by 13 x = 143 / 13 = 11

*posted on November 29, 2018* -
## Math

ln M = - 0.12 t + 4.67 M = e ^ ( - 0.12 t + 4.67 ) M = e ^ ( - 0.12 t ) * e ^ 4.67 M = [ e ^ ( - 0.12 ) ] ^ t * e ^ 4.67 M = 0.88692 ^ t * 106.69774 M = 106.69774 * 0.88692 ^ t So: M = a * b ^ t a = 106.69774 , b = 0.88692

*posted on November 27, 2018* -
## Calculus

You have Reiny's answer on this page. Calculus - Anonymous today at 4:14pm Calculus - Reiny today at 4:49pm Calculus - Anonymous today at 6:13pm

*posted on November 22, 2018* -
## Calculus

The point-slope forms straight line equation : y − y1 = m ( x − x1 ) In this case x1 = 1 y1= eˣ¹ = e¹ = e m = slope = first derivation in point x = 1 m = eˣ¹ = e¹ = e y − y1 = m ( x − x1 ) y − e = e ( x − 1 ) y − e = e ∙ x − e ∙ 1

*posted on November 22, 2018* -
## Math

n = a ∙ b a = smaller number b = greater number One of the products of a number is 7 times of the other one mean: b = 7 a The number is 63 mean: n = a ∙ b = 63 Replace b = 7 a in this equation. a ∙ 7 a = 63 7 a² = 63 Divide both sides by 7 a² = 63

*posted on November 20, 2018* -
## Maths

The horizonatal length is x and the vertical length is y. Rearrange 3 x + 2 y = 6 2 y = 6 - 3 x 2 y = - 3 x + 6 y = ( - 3 x + 6 ) / 2 y = - 3 x / 2 + 3 A = x ∙ y = x ∙ ( - 3 x / 2 + 3 ) = - 3 x² / 2 + 3 x dA / dy = y´= - 3 ∙ 2 x / 2 + 3 = - 3 x + 3

*posted on November 19, 2018* -
## math

2 / 3 ∙ 100% = 0.6666... ∙ 100% = 66.666...% = 66 2/3%

*posted on November 16, 2018* -
## math

0.709 ∙ 100% = 70.9 %

*posted on November 16, 2018* -
## math

My typo: it is written x - 7 / 32 = ± √ [ ( - 1 ) ∙ √15 ] / 32 should be x - 7 / 32 = ± √ [ ( - 1 ) ∙ 15 ] / 32

*posted on November 16, 2018* -
## math

16 x² + 1 = 7 x Subtract 7 x to both sides 16 x² + 1 - 7 x = 7 x - 7 x 16 x² - 7 x + 1 = 0 Divide both sides by 16 x² - 7 x / 16 + 1 / 16 = 0 Subtract 1 / 16 to both sides x² - 7 x / 16 + 1 / 16 - 1 / 16 = 0 - 1 / 16 x² - 7 x / 16 = - 1 / 16 Add [ (

*posted on November 16, 2018* -
## math

In a right triangle, square on the hypotenuse is equal to sum of the squares on the other two sides. Here, other two sides as it is an isosceles right triangle. Let these sides be each x inches. x² + x² = 22² 2 x² = 484 Divide both sides by 2 x² = 242

*posted on November 16, 2018* -
## Math

65 = 1 ∙ 5 ∙ 13

*posted on November 9, 2018* -
## algebra

Go on: wolframalpha.c o m When page be open in rectangle type: plot y= 1/x and clck option = you will see graph Then type: plot y= 5/(x+6) and clck option = ___________________________________ Remark: You must type plot y= 5/(x+6) with brackets

*posted on November 9, 2018* -
## math

x intercept is a point where f(x) = 0 So you must sove equation: - 6 x² + 2 700 x - 63 750 = 0 - 6 ∙ ( x² - 450 x + 10 625 ) = 0 Divide both sides by - 6 x² - 450 x + 10 625 = 0 Solve this equation usngquadratic formula. x₁/₂ = [ - b ± √ ( b²

*posted on November 8, 2018* -
## Math

- 7 / 9 ∙ 3 / 5 = - 7 ∙ 3 / 9 ∙ 5 = - 7 ∙ 3 / 3 ∙3 ∙ 5 = - 7 / 3 ∙ 5 = - 7 / 15

*posted on November 8, 2018* -
## Math

( 8 x - 5 ) / ( 12 x + 3 ) = 5 / 9 cross multiply ( 8 x - 5 ) ∙ 9 = 5 ∙ ( 12 x + 3 ) 8 x ∙ 9 - 5 ∙ 9 = 5 ∙ 12 x + 5 ∙ 3 72 x - 45 = 60 x + 15 Subtract 60 x to both sides 72 x - 45 - 60 x = 60 x + 15 - 60 x 12 x - 45 = 15 Add 45 to both sides 12

*posted on November 8, 2018* -
## Math

Make sure you write the equation correctly. Solution of the equation y = - 4 x ^ 2 is x = 0 , y = 0 or ordered pairs ( 0 , 0 )

*posted on November 7, 2018* -
## math

a = cost of aples p = cost of ponkans You must solve system of two equations: 3 a + 2 p = 51 2 a + 3 p = 46.5 ____________ The solutions are: a = 12 , p =7.5 Half a dozen apples and half a dozen ponkans cost: a / 2 + p / 2 = 12 / 2 + 7.5 / 2 = 6 + 3.75 =

*posted on November 6, 2018* -
## Math

Yes because 14 / 2 = 7

*posted on November 6, 2018* -
## math

There is nothing to simplify here. It's already simplified.

*posted on November 5, 2018* -
## Math

replace g with - 2 - 5 g - 6 = - 5 ∙ ( - 2 ) - 6 = 10 - 6 = 4

*posted on November 2, 2018* -
## math

3 1/5 = 3 + 1 / 5 = 3 ∙ 10 / 10 + 2 ∙ 1 / 2 ∙ 5 = 30 / 10 + 2 / 10 = 32 / 10 6 1/2 = 6 + 1 / 2 = 6 ∙ 10 / 10 + 5 ∙ 1 / 5 ∙ 2 = 60 / 10 + 5 / 10 = 65 / 10 - 3 1/5 + ( - 6 1/2 ) = - 3 1/5 - 6 1/2 = - 32 / 10 - 65 / 10 = - ( 32 / 10 + 65 / 10 ) =

*posted on November 2, 2018* -
## math

You're welcome.

*posted on November 2, 2018* -
## math

1 / 2 = 3 ∙ 1 / 3 ∙ 2 = 3 / 6 1 / 3 = 2 ∙ 1 / 2 ∙ 3 = 2 / 6 - 1 / 2 + 1 / 3 = - 3 / 6 + 2 / 6 = 2 / 6 - 3 / 6 = - 1 / 6

*posted on November 2, 2018* -
## math

S = smaller number. L = larger number = 54 S / L = 7 / 9 S / 54 = 7 / 9 Cross multiply: 9 ∙ S = 54 ∙ 7 9 S = 378 Divide both sides by 9 S = 378 / 9 S = 42 Proof: 42 / 54 = 6 ∙ 7 / 6 ∙9 = 7 / 9

*posted on October 28, 2018* -
## algebra

If your question mean: log₈( x³ ) = 4 then: 3 ∙ log₈ ( x ) = 4 log₈ ( x ) = 4 / 3 x = 8 ^ ( 4 / 3 ) x = ∛ 8⁴ x = ∛ 4096 x = 16

*posted on October 27, 2018* -
## math

Two series alternate here. In the first series, 3 is added to each number to arrive at the next. 4, 7, 10 , __ , 16, 19 In the second series, 5 is subtracted from each number to arrive at the next. 25 , 20 ... Your number is in the first series. So you

*posted on October 26, 2018* -
## Math

19 = h / 3 - 8 Multiply both sides by 3 57 = h - 24 Add 24 both sides 57 + 24 = h - 24 + 24 81 = h h = 81

*posted on October 26, 2018* -
## Math

52 + g = 45 + 11 52 + g = 56 52 + 4 = 56 g = 4 Answer C

*posted on October 26, 2018* -
## Math

If your question mean. Prove: cos² ( θ ) / [ 1 - tan ( θ ) ] + sin³ ( θ ) / [ sin ( θ ) - cos ( θ ) ] = 1 + sin ( θ ) ∙ cos ( θ ) then cos² ( θ ) / [ cos ( θ ) / cos ( θ ) - sin ( θ ) / cos ( θ ) ] + sin³ ( θ ) / [ sin ( θ ) - cos ( θ

*posted on October 25, 2018* -
## Algebra

For all values of x, y = - 6 Your function: y = - 6

*posted on October 25, 2018* -
## Math

1,005 / 8 = ( 1,000 + 5 ) / 8 = 1,000 / 8 + 5 / 8 = 125 5/8 Remainder = 5

*posted on October 25, 2018* -
## Math

Are you kidding? 5 + ( 7 - 8 ) = 5 + 7 - 8 = 12 - 8 = 4

*posted on October 25, 2018* -
## math

Composite number can be written as the product of two or more primes. In this case: 25 = 5 ∙ 5 Answer C

*posted on October 25, 2018* -
## math

The other sides : x and x + 1 where x + 1 is the hypotenuse So Pythagorean theorem: ( x + 1 )² = x² + 15² x² + 2 x + 1 = x² + 225 Both x² get cancelled 2 x + 1 = 225 2 x = 225 - 1 = 224 x = 224 / 2 = 112 m Hypotenuse: x + 1 = 112 + 1 = 113 m

*posted on October 23, 2018* -
## Math

a2 = - 7 , a5 = 56 nth term in GP: an = a1 ∙ r ⁿ⁻¹ where: a1 = first term , r = common ratio a2 = a1 ∙ r ²⁻¹ = r¹ = a1 ∙ r a5 = a1 ∙ r ⁵⁻¹ = a1 ∙ r ⁴ a5 = a1 ∙ r ∙ r ³ a5 = a2 ∙ r ³ 56 = ( - 7 ) ∙ r ³ Divide both sides

*posted on October 22, 2018* -
## math

37 1/2 % = 37.5 % = 37.5 / 100 = 375 / 1000 = 125 ∙ 3 / 125 ∙ 8 = 3 / 8 37 1/2 % = 3 / 8

*posted on October 21, 2018* -
## Math

The sum of n terms of an AP: Sn = ( n / 2 ) ∙ [ 2 a1 + ( n - 1 ) ∙ d ] The sum of 16 terms of an AP: S16 = ( 16 / 2 ) ∙ [ 2 a1 + ( 16 - 1 ) ∙ d ] S16 = 8 ∙ [ 2 a1 + 15 d ] = - 504 8 ∙ 2 a1 + 8 ∙ 15 d = - 504 16 a1 + 120 d = - 504 The sum of 9

*posted on October 21, 2018* -
## Math

Volume of a metal block of length 4 cm, breadth 3 cm and height 2.5 cm V = L ∙ B ∙ H V = 4 ∙ 3 ∙ 2.5 = 30 cm³ mass = 500 g Density : ρ = m / V = 500 / 30 = 10 ∙ 50 / 10 ∙ 3 = 50 / 3 ( g / cm³ ) Volumea block of length 5cm , breadth 4c m,a nd

*posted on October 21, 2018* -
## Math

Each inch of the necklace has 3 beads. You don't care about how many spacers. The total number of beads is the product = number of beads per inch * number of inche. In this case: x = Necklace length (number of inches) y = How many beads depends on x

*posted on October 18, 2018* -
## math

Linear sequence is other name for arithmetic sequence. For arithmetic sequence nth term: an = a1 + ( n - 1 ) d where: a1 = initial term of arithmetic progression d = common difference In this case: a5 = a1 + ( 5 - 1 ) d a5 = a1 + 4 d a10 = a1 + ( 10 - 1 )

*posted on October 15, 2018* -
## Maths

In A.P. a1 = initial term of arithmetic progression d = common difference nth term of A.P. an = a1 + ( n - 1 ) d In this case a1 = x , a2 = 3 x + 1 , a3 = 7 x - 4 so: a1 = x a2 = a1 + ( 2 - 1 ) d a2 = a1 + d 3 x + 1 = x + d a3 = a1 + ( 3 - 1 ) d a3 = a1 +

*posted on October 14, 2018* -
## MATH

The frist term of an A.P is equal to twice the common difference d mean: a1 = 2 d nth term of the A.P: an = a1 + ( n - 1 ) d a5 = a1 + ( 5 - 1 ) d a5 = a1 + 4 d Since a1 = 2 d a5 = a1 + 4 d = 2 d + 4 d = 6 d a5 = 6 d

*posted on October 10, 2018* -
## math

- 4 y + 8 = 4 ( 2 y - 2 ) - 2 ( - 16 + 8 y ) - 4 y + 8 = 4 ∙ 2 y + 4 ∙ ( - 2 ) - 2 ∙ ( - 16 ) - 2 ∙ 8 y - 4 y + 8 = 8 y - 8 + 32 - 16 y - 4 y + 8 = 8 y - 16 y - 8 + 32 - 4 y + 8 = - 8 y + 24 Add 8y to both sides - 4 y + 8 y + 8 = - 8 y + 8 y + 24 4

*posted on October 9, 2018* -
## math

Mathematical statements with one or more VARIABLES are called open sentences. In statement: 4y + 8 = 6y + 3 variable is y

*posted on October 9, 2018*